Anomalous Diffusion with an Irreversible Linear Reaction and Sorption-Desorption Process - Maike A. F. dos Santos; Marcelo K. Lenzi; Ervin K. Lenzi (Advances in Mathematical Physics)
We investigate the diffusion of two different species in a semi-infinite medium considering the presence of linear reaction terms. The dynamics for these species is governed by fractional diffusion equations. We also consider the presence of an adsorption-desorption boundary condition. The solutions for this system are found in terms of the H function of Fox and by analyzing the behavior of the mean square displacement a rich class of diffusion processes is verified. In this sense, we show how the surface effects modify the bulk dynamics and promote an anomalous diffusion of system.